PEMBIYAAN PENDIDIKAN TINGGI - Busthomi Ibrohim (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2017)
The BHMN implementation policy for a number of State Universities (PTN) may continue. This policy resulted in the consequences of tuition fees becoming more expensive, because the university sought shortcuts to address the shortage of funds by way of SPP. Understandable if this step invites protests from students, parents and the community, because they have to spend up to tens of millions of dollars to be able to study at these respected universities. The concept of higher education by the government that is considered too burdensome state budget is observed with the emergence of the concept of educational education through corporations called corporat corporacy. The benefits of higher education for individuals are increased salaries and income, wider employment options, greater savings, and the kind of work and workplace. The economic benefits of higher education are increased tax revenues, increased productivity, increased consumption, increased labor adaptability and reduced dependence on government financial aid. The benefit for the community is the improvement of welfare. And the benefit for college itself is the improvement of college quality. Keywords. BHMN, Education Policy, PTN, SPP, Corporate Corporate